The Revolution of Food Delivery: How Online Food Delivery Systems are Transforming the Operation Models of Dining Enterprises - Shiqiang Yan; Sidah Idris; Hanum Rania Belfaqeeh (Asian Scholars Network, 2023)
The purpose of this article is twofold. First, it aims to systematically summarize the main research on restaurant operations in the context of takeout, thereby forming a systematic understanding of the current research status. Second, it seeks to propose directions for future research by systematically summarizing previous studies and comparing the concerns of scholars and practitioners. Approach: This work undertakes a comprehensive analysis of the existing literature on the subject by examining 49 highly referenced articles. This paper categorizes research in this field into five distinct themes: customer satisfaction, customer evaluation, delivery model selection, marketing strategy, repurchase behavior, and customer attitude. The primary findings and methodologies for each topic are summarized individually. The main research results and methods for each topic are summarized individually. Through semi-structured interviews, the views of practitioners on research hotspots and future research directions in this field are gathered. Finally, by comparing the concerns of practitioners and scholars, the primary directions for future research are proposed. Significance: This article offers insights for scholars by analyzing and categorizing relevant literature on restaurant operations in the context of food delivery. It also suggests directions for future research activities based on a comparison between the concerns of scholars and practitioners.